2007
DOI: 10.1161/strokeaha.106.477380
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Associations Between the Presence of Acute Ischemic Lesions on Diffusion-Weighted Imaging and Clinical Predictors of Early Stroke Risk After Transient Ischemic Attack

Abstract: Background and Purpose-Early risk of stroke after a transient ischemic attack can be reliably predicted with risk scores based on clinical features of the patient and of the ischemic event, but it is unclear how these features correlate with findings on brain imaging. Methods-We performed a systematic review of the literature and identified all previous studies which reported patient characteristics and the nature of transient ischemic attack symptoms in relation to appearances on diffusion-weighted imaging (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
88
7
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(107 citation statements)
references
References 40 publications
(76 reference statements)
9
88
7
3
Order By: Relevance
“…19 Other factors previously associated with DWI lesions, including speech impairment, atrial fibrillation, and ICA stenosis Ն50%, were not confirmed in our study.…”
contrasting
confidence: 69%
See 1 more Smart Citation
“…19 Other factors previously associated with DWI lesions, including speech impairment, atrial fibrillation, and ICA stenosis Ն50%, were not confirmed in our study.…”
contrasting
confidence: 69%
“…[8][9][10][11][12][13][14][15][16][17][18] These studies were recently compiled in a systematic review. 19 The rate of positive DWI varied from 16 to 67% among suspected TIA cases. Therefore, DWI appears to be a valuable tool to confirm an ischemic etiology in patients with transient neurologic focal symptoms.…”
mentioning
confidence: 99%
“…Molecular and cellular processes responsible for plaque composition [94][95][96] may be more important than the degree of stenosis in determining the risk of stroke, but the severity of stenosis forms the basis for most clinical decision making.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…15 Although developed for use in cohorts of patients before investigation, the possibility has been raised that prognostication might be improved after evaluation in secondary care by the incorporation of information from investigations, particularly the presence of brain infarction on imaging. 3,6 However, patients with high ABCD 2 scores are more likely to have brain infarction on diffusion-weighted imaging (DWI) 16 and so the additional predictive value of a composite score is uncertain. Studies published thus far have been too small to address this issue reliably, far too small to determine appropriate weighting for any imaging features, and meta-analysis of published data is undermined by inconsistent definitions of abnormality on imaging.…”
mentioning
confidence: 99%